2014
DOI: 10.1007/s00198-014-2831-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of forearm fractures in adults in Denmark: national age- and gender-specific incidence rates, ratio of forearm to hip fractures, and extent of surgical fracture repair in inpatients and outpatients

Abstract: The rates of forearm fracture in Denmark are higher than previously estimated and very similar to the high risk reported from studies in Norway and Sweden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 20 publications
(27 reference statements)
1
26
1
Order By: Relevance
“…A total of 14.9 % of women and 5.2 % of men reported a previous low-energy fracture, comparable to rates among women in Denmark of 11.5 % [12] and supporting newly published incidence rates of forearm fractures from Denmark similar to studies from Sweden and Norway [26]. For women above 65 years of age, the reported prevalence was 23.6 %, comparable to 29.7 % of US citizens using Medicare estimates for the USA [27] but higher than official estimates for Denmark and Sweden [28].…”
Section: Discussionsupporting
confidence: 79%
“…A total of 14.9 % of women and 5.2 % of men reported a previous low-energy fracture, comparable to rates among women in Denmark of 11.5 % [12] and supporting newly published incidence rates of forearm fractures from Denmark similar to studies from Sweden and Norway [26]. For women above 65 years of age, the reported prevalence was 23.6 %, comparable to 29.7 % of US citizens using Medicare estimates for the USA [27] but higher than official estimates for Denmark and Sweden [28].…”
Section: Discussionsupporting
confidence: 79%
“…However, their findings must be interpreted with care as they included only one fracture per individual, rendering a decreasing population at risk with successive years without a corresponding decrease in the denominator and without adjustment for lower risks in those who remained eligible. On the other hand Abrahamsen et al [4] in a recent large register based study in Denmark, found a higher incidence compared to earlier. Their reported incidence for men (153 per 100,000 py) was nearly the same as we found, but for women (530 per 100,000 py) somewhat higher (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…After the 1980’s some studies have reported decreasing or stable adult distal forearm fracture rates [5, 1320], whilst some recent reports, from Denmark and Taiwan, infer an increasing incidence [4, 21] (Fig. 3a, b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations